PEMBUATAN SISTEM PENCATATAN STOK PADA TOKO AGUNG JAYA DENGAN MENGGUNAKAN APLIKASI MICROSOFT ACCESS - Marheni, Dewi Khornida; Kristina, Kristina (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
This community service was carried out with the aim of designing a Microsoft Access-based stock recording system to make it easier for Toko Agung Jaya, which is a store that provides building materials, to operate. Agung Jaya Store, which has been operational for 21 years, still does not have a correct stock recording method, so storage management still seems messy. In order to correct deficiencies in the shop, a system was designed to suit the partners’ needs, starting with collecting information using observation and interview methods. After obtaining the required information, the next step is to develop a system based on the data that has been collected. Apart from that, testing is carried out to see whether the system is suitable for use and can make things easier for partners. The implementation stage is carried out by converting partner storage data into a stock recording system that has been designed. The final stage of this service is training partners in using the system and making reports. The designed system has been successfully implemented and is able to meet the needs of partners so that this service to the community is considered successful.